The Impact of the Amundsen Sea Freshwater Balance on Ocean Melting of the West Antarctic Ice Sheet - Bett, David T.; Holland, Paul R.; Naveira Garabato, Alberto C.; Jenkins, Adrian; Dutrieux, Pierre; Kimura, Satoshi; Fleming, Andrew (Journal of Geophysical Research: Oceans, 2020)
The Amundsen Sea has the highest thinning rates of ice shelves in Antarctica. This imbalance is caused by changes in ocean melting induced by warm Circumpolar Deep Water (CDW) intrusions. The resulting changing freshwater balance could affect the on‐shelf currents and mixing. However, a clear understanding of the sources and sinks of freshwater in the region is lacking. Here we use a model of the Amundsen Sea, with passive freshwater tracers, to investigate the relative magnitudes and spatial distributions of the different freshwater components. In the surface layer and as a depth average, all freshwater tracer concentrations are of comparable magnitude, though on a depth average, sea ice and ice shelf are largest. The total freshwater tracer distribution is similar to that of the ice‐shelf tracer field. This implies a potential for ice‐shelf meltwater feedbacks, whereby abundant ice‐shelf meltwater alters the ocean circulation and stratification, affecting melting. Ice‐shelf and sea‐ice freshwater fluxes have the largest interannual variability. The effect of including grounded icebergs and iceberg freshwater flux are studied in detail. The presence of icebergs increases CDW intrusions that reach the base of ice shelves. This suggests another possible feedback mechanism, whereby more icebergs induce greater ice‐shelf melting and hence more icebergs. However, the strength of this potential feedback is dependent on poorly constrained sea‐ice model parameters. These results imply that poorly constrained parameters relating to the ocean freshwater balance, such as those relating to icebergs and sea ice, impact predictions for melting of the West Antarctic Ice Sheet.